The Meaning of College Education for Working Student - Usman, Ari (International Journal of Linguistics, Communication, and Broadcasting, 2025)
This study explores the meaning of college education for working students, who experience a different academic journey compared to regular students. Using a qualitative method with a phenomenological approach, data were collected through interviews, observation, and literature study. The findings show that working students view college as an act of financial independence, a form of self-actualization, a means to gain knowledge, and a way to achieve a better future. These insights reflect the deeper personal and professional significance of higher education in the lives of students who balance work and study. The study reveals how working students manage time, energy, and responsibilities to pursue their academic goals. The results provide valuable input for educational institutions in supporting the unique needs of this student group.